CHILE, LA CATÁSTROFE SOCIAL - Marín, Francisco (La Sociología en sus Escenarios, 2010)
Abstract. Beyond the disaster, the earthquake in Chile removed to the surface "to the social monster that is hidden" and exhibited "myths about the development" of this country, maintains to the historian Gabriel Salazar. The vandalism that followed the catastrophe added to the lack of coordination of official institutions that had to alert to the coastal population on tsunami that it swept to several towns and it caused the death of at least 400 people Resumen. Más allá del desastre, el terremoto en Chile sacó a la superficie "al monstruo social que está oculto" y exhibió "los mitos acerca del desarrollo" de este país, sostiene el historiador Gabriel Salazar. El vandalismo que siguió a la catástrofe se sumó a la descoordinación de instituciones oficiales que debieron alertar a la población costera sobre el tsunami que barrió a varios poblados y causó la muerte de al menos 400 personas.